Evaluating the diagnostic accuracy of maximal aortic diameter, length and volume for prediction of aortic dissection. Issue 12 (8th March 2020) - Heuts, Samuel; Adriaans, Bouke P; Rylski, Bartosz; Mihl, Casper; Bekkers, Sebastiaan C A M; Olsthoorn, Jules R; Natour, Ehsan; Bouman, Heleen; Berezowski, Mikolaj; Kosiorowska, Kinga; Crijns, Harry J G M; Maessen, Jos G; et al.
Abstract : Objective: Management of thoracic aortic aneurysms (TAAs) comprises regular diameter follow-up until the indication criterion for prophylactic surgery is reached. However, this approach is unable to predict the majority of acute type A aortic dissections (ATAADs). The current study aims to evaluate the diagnostic accuracy of ascending aortic diameter, length and volume for occurrence of ATAAD. Methods: This two-centre observational cohort study retrospectively screened 477 consecutive patients who presented with ATAAD between 2009 and 2018. Of those, 25 (5.2%) underwent CT angiography (CTA) within 2 years before dissection onset. Aortic diameter, length and volume of these patients ('pre-ATAAD') were compared with those of TAA controls (n=75). Receiver operating curve analysis was performed to evaluate the predictive accuracy of the three different measurements. Results: 96% of patients with pre-ATAAD did not meet the surgical diameter threshold of 55 mm before dissection onset. Maximal aortic diameters (45 (40–49) mm vs 46 (44–49) mm, p=0.075) and volume (126 (95–157) cm 3 vs 124 (102–136) cm 3, p=0.909) were comparable between patients with pre-ATAAD and TAA controls. Conversely, ascending aortic length (84±9 mm vs 90±16 mm, p=0.031) was significantly larger in patients with pre-ATAAD. All three parameters had an area under the curve of >0.800. At the 55 mm cut-off point, the maximal diameter yielded a positive predictive value (PPV) of 20%. While maintaining same specificity levels, measurements of aortic volume and length showed superior diagnostic accuracy (PPV 55% and 70%, respectively). Conclusion: Measurements of aortic volume and length have superior diagnostic accuracy compared with the maximal diameter and could improve the timely identification of patients at risk for ATAAD.